Let it snow! Winter conditions affect growth of birch seedlings during the following growing season. (4th December 2018) - Domisch, Timo; Martz, Françoise; Repo, Tapani; Rautio, Pasi
Abstract: Air temperatures and precipitation are predicted to increase in the future, especially at high latitudes and particularly so during winter. In contrast to air temperatures, changes in soil temperatures are more difficult to predict, as the fate of the insulating snow cover is crucial in this respect. Soil conditions can also be affected by rain-on-snow events and warm spells during winter, resulting in freeze–thaw cycles, compacted snow, ice encasement and local flooding. These adverse conditions during winter could counteract the otherwise positive effects of climate change on forest growth and productivity. For studying the effects of different winter and snow conditions on young Downy birch ( Betula pubescens Ehrh.) seedlings, we carried out a laboratory experiment with birch seedlings subjected to four different winter scenarios: snow covering the seedlings (SNOW), compressed snow and ice encasement (ICE), flooded and frozen soil (FLOOD) and no snow at all (NO SNOW). After the winter treatments we simulated a spring and early summer period of 9.5 weeks, and monitored the growth by measuring shoot and root biomass of the seedlings, and starch and soluble sugar concentrations. We also assessed the stress experienced by the seedlings by measuring leaf chlorophyll fluorescence and gas exchange. Although no difference in mortality was observed between the treatments, the seedlings in the SNOW and ICE treatments had significantly higher shoot and root biomass compared with those in the FLOOD and NO SNOW treatments. We found higher starch concentrations in roots of the seedlings in the SNOW and ICE treatments, compared with those in the FLOOD and NO SNOW treatments, although photosynthesis did not differ. Our results suggest a malfunction of carbohydrate distribution in the seedlings of the FLOOD and NO SNOW treatments, probably resulting from decreased sinks. The results underline the importance of an insulating and protecting snow cover for small tree seedlings, and that future winters with changed snow pattern might affect the growth of tree seedlings and thus possibly species composition and forest productivity.